Evaluation of BACTEC MYCO/F Lytic Medium for Recovery of Mycobacteria, Fungi, and Bacteria from Blood - Fuller, DeAnna D. (American Society for Microbiology, 2001)
MYCO/F Lytic medium (MFL), a liquid medium developed for use with the BACTEC 9240 blood culture system, was compared to the Isolator system (IS) for the recovery of fungi and to the BACTEC 13A medium for the recovery of mycobacteria. Recovery of bacteria was compared to routine BACTEC Plus Aerobic/F (AF) blood cultures. Microbial growth was detected in 203 (17%) of 1,166 blood cultures. Fifty-seven specimens were positive for fungi: 35 were positive with both IS and MFL; six were positive with IS only (three Candida albicans, one Histoplasma capsulatum, one Candida glabrata, and one Fusarium species isolate); three were positive with AF only (two C. albicans and one Candida parapsilosis isolate); and 13 were positive with MFL only (five C. glabrata, three C. albicans, two Candida krusei, two Candida tropicalis, and one C. parapsilosis isolate; P > 0.05 versus IS). Eighteen of 19 blood cultures positive for H. capsulatum grew in both IS and MFL, although the time to detection for MFL was greater. The mean time to detection for all fungi was 8.15 days for IS and 12.07 days for MFL. Seven hundred forty specimens were also cultured for mycobacteria with MFL and 13A. Forty-four grew mycobacteria; 38 were positive with both 13A and MFL; and 16 were positive with MFL only. Mycobacterium avium was recovered from 41 specimens; 36 were positive for both systems and 5 were positive for MFL alone. MFL was also compared to the AF bottle for the same 740 specimens. MFL and AF both detected 34 of the 40 clinically significant bacteria, while IS detected only 15 of 40. In summary, MFL is an excellent medium for the recovery of fungi, mycobacteria, and bacteria; however, the time to detection of H. capsulatum is increased.